Impacts of Bacillus amyloliquefaciens and Trichoderma spp. on Pac Choi (Brassica rapa var. chinensis) grown in different hydroponic systems - Plocek, Gretchen; Rueda Kunz, Dario; Simpson, Catherine (Frontiers in Plant Science, 2024)
Soilless production systems (i.e hydroponics, aeroponics, aquaponics) have become commonplace in urban settings and controlled environments. They are efficient nutrient recyclers, space savers, and water conservers. However, they lack high levels of biological richness in the root microbiome when compared to soil production systems, which may affect plant health and nutrient uptake.. To address this issue and incorporate more sustainable practices, beneficial microorganisms (i.e. Trichoderma spp., Bacillus sp.) can be added in the form of biofertilizers. However, many factors affect impacts of microorganisms and their interactions with plants. In this experiment, Black Summer Pac Choi (Brassica rapa var. Chinensis) was grown for two trials in a Deep-Water system (DWS) or a Nutrient Film Technique system (NFT) with commercial biofertilizers containing Trichoderma spp., Bacillus amyloliquefaciens, a combination of both, and a control. Plant physiology, nutrient composition, and nutrient uptake efficiency (NUE) were generally negatively affected by Trichoderma spp. both growing systems, indicating that Trichoderma may not be recommended for hydroponic production. However, Bacillus amyloliquefaciens showed promise as an effective biofertilizer in the NFT systems and had a positive influence on NUE in DWS. Biofertilizers are generally defined as mixtures of microorganisms (e.g., fungi, bacteria) added to the rooting environment to promote a crop's growth, plant health, and nutrient uptake (Daniel et al., 2022;Mohammadi & Sohrabi, 2012;Zhao et al., 2024). Due to the positive associations that can be formed, these can also be termed beneficial microorganisms. Various microorganisms, such as Bacillus spp., Trichoderma spp., Azospirillum spp., and Pseudomonas spp., can be used as biofertilizers. (Reed & Glick, 2023). Inoculations can be made through lab-grown populations or more easily accessible commercial products. Often, mixtures are added to the rhizosphere of crops grown in soil to achieve the desired effects of increased growth, biomass, and harvestable material (Dasgan et al., 2023). However, these desired effects may not be as easily reached in hydroponics due to rhizosphere environmental differences between soil-based and soilless production systems and compatibility challenges with various crops.Biofertilizers used in hydroponic systems have varied in composition and ranged from microalgae (Chlorella vulgaris), arbuscular mycorrhizal fungi (AMF), plant growth promoting rhizobacteria (PGPR),